Communication Climate at Work Fostering Friendly Friction in Organisations - Kvalnes, Øyvind (Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores how members of an organization or group speak to and with each other. An expansion of the author's previous research on fallibility in organizations, the concept of communication climate is related to those of voice climate and psychological safety, both of which focus on the risk of speaking up and raising concerns at work. In this book the author addresses the scope for criticism, dissent and disagreement, but also for praise and encouragement. Beginning with a clear explanation of how and why communication climate is important in organizations, the author introduces the concept of critical quality moments, i.e. situations where a verbal intervention can crucially change the course of events for the better. The book then goes on to describe seven elements that characterize well-functioning communication climates before exploring the concept of communication ethics, and the balance between freedom of speech on the one hand, and speech responsibility on the other. It concludes with suggestions for further studies of communication climate at work. This is an open access book. Øyvind Kvalnes is Professor in the Department of Leadership and Organizational Behaviour at BI Norwegian Business School, Norway. He has facilitated workshops and seminars on communication climate in a range of organisations in the private and public sectors. He is the author of Fallibility at Work (2017), Digital Dilemmas (2020) and Moral Reasoning at Work (2019), all published by Palgrave Macmillan, Øyvind's main research interests are in communication climate, , ethics, moral psychology, leadership, and excellence in organizations.